Influence mechanisms of professional managers in family business succession - Li Ying (2022)
Family businesses have a pivot al market position. In recent years, the first family businesses in China have entered the stage of old age, which makes them face severe problems of intergenerational succession . This study explores the intergenerational succ essi on of family businesses in China , based on the resource based view, principal agent theory, entrepreneur theory and stakeholder theory to discuss the influence mechanism of professional managers in the intergenerational succession of family businesses Firstly , data were obtained b y interviews with incumbent entrepreneurs, successor entrepreneurs and professional managers A qualitative research method grounded theory was used to construct a conceptual model. Secondly, the hypothes e s were put forward on t he mechanism of profession al managers on intergenerational succession . Thirdly, items were summarized based on the results of the interview and scales were developed through data collection from questionnaire survey and exploratory factor analysis. Last, data were collected again through a questionnaire survey , and the conceptual model was tested using structural equation modeling. Research findings : a) Professional managers can indirectly promote the success of succession by cultivating successor entrepreneurs competence. b) Professional managers can indirectly promote the success of succession by alleviating the conflict between the two generations o f entrepreneurs. The management implications are a Family businesses can consider hiring professional managers to help two generations of entrepreneurs go through the transition period smoothly. b) Incumbent entrepreneurs should pay attention to all aspects of competence when selecting professional managers. c) Family businesses should take reasonable incentive measures to motivate professional managers to continuously improve their competence.